2005
DOI: 10.1364/ao.44.001332
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of aerosol refractive index from extinction spectra with a damped harmonic-oscillator band model

Abstract: A new method for the retrieval of the spectral refractive indices of micrometer-sized particles from infrared aerosol extinction spectra has been developed. With this method we use a classical damped harmonic-oscillator model of molecular absorption in conjunction with Mie scattering to model extinction spectra, which we then fit to the measurements using a numerical optimal estimation algorithm. The main advantage of this method over the more traditional Kramers-Kronig approach is that it allows the full comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…For example, when both refractive indices and particle size parameters are to be extracted from large aerosol particle spectra, the CDHO fitting can be employed where only a handful of parameters are need optimisation. 37,48 Based on the quantitative analysis in this study, we conclude that the Fourier series fitting is the most desirable method, especially when spectral features are not very narrow (> 10 cm -1 ). In cases where the spectral features are narrow (< 10 cm -1 ) the CDHO and the Triangular fitting are the most accurate and fast of the four methods.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…For example, when both refractive indices and particle size parameters are to be extracted from large aerosol particle spectra, the CDHO fitting can be employed where only a handful of parameters are need optimisation. 37,48 Based on the quantitative analysis in this study, we conclude that the Fourier series fitting is the most desirable method, especially when spectral features are not very narrow (> 10 cm -1 ). In cases where the spectral features are narrow (< 10 cm -1 ) the CDHO and the Triangular fitting are the most accurate and fast of the four methods.…”
Section: Discussionmentioning
confidence: 67%
“…Also note that the fitting is fastest (a few seconds) for the CDHO method due to its analytic nature and availability of analytic derivatives. 37 The triangular fitting converges similarly fast. The Fourier series fitting is also fast (tens of seconds), and it may be possible to accelerate further by evaluating series coefficients by Fast Fourier Transform.…”
Section: Fitting Of Acetonitrilementioning
confidence: 88%
See 1 more Smart Citation
“…Aerosols' IR optical properties during the ACE-Asia campaign were measured (Markowicz et al, 2003), and it was shown that the mean aerosol optical depth at 10 µm was 0.08 (for the entire atmospheric column). Apart from the complete optical depth, aerosol optical properties in the LWIR have been studied (Thomas et al, 2005;Richwine et al, 1995;Toon et al, 1976;Volz, 1972Volz, , 1973, and in addition, the effect of changes in the relative humidity on the extinction coefficients of atmospheric aerosols was presented (Nilsson, 1979). These properties can be incorporated in radiative transfer models in order to determine aerosols' radiative effect.…”
Section: Aerosolsmentioning
confidence: 99%
“…et al, 1996). Laboratory based refractive indices estimation methods with spectral extinction measurements are proposed (Eiden R., 1971, Thomas G.E., et al, 2005. Refractive index and size distribution as well as single scattering albedo, Angstrome exponent, volume spectrum are, in general, estimated with ground based solar direct, diffuse and aureole data together with measured optical depth.…”
Section: Introductionmentioning
confidence: 99%